ANALYSIS OF THE REGIONAL FINANCE INDEPENDENCE OF TRENGGALEK REGENCY - Mudrifah Mudrifah; Rika Wahyuningtyas (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2021)
The purpose of this study is to determine the differences in the level of regional financial independence of the Trenggalek Regency Government for the period 2014-2016 and the period 2017-2019. This research uses comparative research. The type of data in this study is secondary data with documentation data collection techniques. The data source used is sourced from the Directorate General of Fiscal Balance's website at the Central and Regional Government Offices (DJPK). The data analysis technique used in this research is the descriptive analysis technique. The type of data in this study is secondary data with documentation data collection techniques.  The results show that the ratio level of the degree of fiscal decentralization in Trenggalek was in a low category. It happened in the period 2014-2016 and the period 2017-2019. The value of regional financial dependency ratios is in the high category in the 2014-2016 and 2017-2019 periods. The value of the regional financial independence ratio is in the poor category in the 2014-2016 period, and the 2017-2019 period is in the low and medium category. The effectiveness ratio's value in the practical category in the 2014-2016 period and the 2017-2019 period.Keywords: Regional Independence, Local Revenue, Regional Income.